Factors Associated with Blood Pressure Control among Hypertensive Patients - Wutthikitcharat, Wanida; Nakawiro, Pakkawee; Bosittipichet, Tatree (Journal of Preventive Medicine Association of Thailand, 2021)
Hypertension is a serious medical condition that significantly increases the risk of heart attack, stroke, kidney failure, and blindness. It is one of the leading causes of premature death worldwide. Of the estimated 1.13 billion people who have hypertension, fewer than 1 in 5 have it under control. Despite growing evidence of factors associated with blood pressure control worldwide but not been sufficiently described in the primary care center in Phra Nakhon Si Ayutthaya Province. This study is aimed to explore associated factors of controllable blood pressure among hypertensive patients in the Phai Ling Tambon Health Promoting Hospital, Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya Province. This study was an Etiognostic exploratory cross-sectional study of 186 hypertensive patients, selected by convenience sampling. Data was collected by interviewing the sample groups from July 2020 to September 2020 by using questionnaires. The data were reported as frequency and percentage and were analyzed by chi-square and multiple logistic regression with statistic significant level at 0.05. The results revealed that the educational level (multivariable odds ratio [mOR] = 5.68, P=0.050, 95%CI = 1.01-32.11), adherence to anti-hypertensive drugs (mOR = 4.53, P=0.009, 95%CI = 1.47-13.97), Thai CV risk score < 10% (mOR = 4.41, P<0.001, 95%CI = 2.08-9.32) was statistically significant association with good blood pressure control but sodium consumption > 2,000 mg./day (mOR = 0.35, P=0.007, 95% CI = 0.16-0.75) was statistically significant association with poor blood pressure control. The results suggested emphasizing lifestyle modification: low-sodium diet consumption, medication adherence, and reduced Thai CV risk score by weight and waist circumference reduction, blood sugar and lipid control by DASH diet, and smoking cessation.